2020
DOI: 10.3390/electronics9061021
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Fleet Management Strategy for On-Demand Mobility Services: A Case Study in Munich

Abstract: The global market for MoD services is in a state of rapid and challenging transformation, with new market entrants in Europe, such as Uber, MOIA, and CleverShuttle, competing with traditional taxi providers. Rapid developments in available algorithms, data sources, and real-time information systems offer new possibilities of maximizing the efficiency of MoD services. In particular, the use of demand predictions is expected to contribute to a reduction in operational costs and an increase in overall service qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Ehlers et al [45] also demonstrated a further possibility for evaluating a mixed fleet based on an economic efficiency compared to other fleet compositions via a Fleet Efficiency Factor. Recent works based on regression methods are focusing on fleet sizing summarized under the term Mobility on Demand for shared bikes [46][47][48][49], cars and taxis [50][51][52]. Similarities can be found also for the optimum mix and size of air taxi fleets in the aviation industry [53][54][55][56].…”
Section: Vehicle Fleet Sizing Problemsmentioning
confidence: 99%
“…Ehlers et al [45] also demonstrated a further possibility for evaluating a mixed fleet based on an economic efficiency compared to other fleet compositions via a Fleet Efficiency Factor. Recent works based on regression methods are focusing on fleet sizing summarized under the term Mobility on Demand for shared bikes [46][47][48][49], cars and taxis [50][51][52]. Similarities can be found also for the optimum mix and size of air taxi fleets in the aviation industry [53][54][55][56].…”
Section: Vehicle Fleet Sizing Problemsmentioning
confidence: 99%
“…Nowadays, in the taxi dispatching domain, the nearest-taxi/nearest-request (NTNR) strategy is often used as baseline. It assigns customers to the closest available taxis if there are more available taxis than customers (like FCFS), but allocates each available taxi to the closest waiting customer if there are less taxis than customers [12,13]. The availability of real-time GPS data streams as well as support for Vehicle-to-Vehicle (V2V) and Vehicle-to-Infrastructure (V2I) communication has spawned interest in novel ICT platforms that support taxi fleet management.…”
Section: Related Workmentioning
confidence: 99%
“…For the high demand location Marienplatz, censoring might have occurred in up to 24% of all data points. Such censored demand only occurs for the carsharing service, but not the taxi service, as taxi street-hailing is less common in Munich [35], and as Munich has a significant oversupply in taxis [36].…”
Section: Censored Demandmentioning
confidence: 99%